Model Pendidikan Inklusif dalam Pembelajaran Sejarah di SMA Negeri 4 Palu - Badria Abdullah (Universitas Negeri Yogyakarta, 2016)
The purpose of this research is to find out : (1) the development of education inclusive in SMAN 4 Palu, and (2) reality of learning of history at SMAN 4 Palu. Research data collected through the interview, observations, and the documentation. This study in the data analysis that are induktif and in the form of interactive are based on the relationship between the fact one and the fact that others who have a causal through the data collection, the reduction, of the data, the presentation of the data, verification data, or the withdrawal of the conclusion. The results of research shows that activity as well as the development of education inclusive in SMAN 4 Palu has been run since 2014, students special needs learn along with the students regular in a class. All of the school support and tried to maximize education inclusive, although in fact still much shortcomings in the implementation of education inclusive. In the learning of history at SMAN 4 Palu is good, according to the implementation to the lives of the day of the day learners adapted in methods, the media, and the material impertinent. Keywords: Inclusive Education, History Learning.